PSMB7 Is a Key Gene Involved in the Development of Multiple Myeloma and Resistance to Bortezomib - Wu, Dong; Miao, Jiyu; Hu, Jinsong; Li, Fangmei; Gao, Dandan; Chen, Hongli; Feng, Yuandong; Shen, Ying; He, Aili (Frontiers in Oncology, 2021)
Multiple myeloma (MM) represents the most significant clinical manifestation in a series of plasma dysplasia and is the second most commonly diagnosed hematologic neoplasm. Monoclonal gammopathy of undetermined significance (MGUS) and smoldering MM (SMM) are the premalignant stages of MM, which can progress to MM approximately 1% or 10% per year, respectively. The overall survival of MM significantly improved by the introduction of proteasome inhibitors (PIs), but almost all of the MM patients relapse and resist anti-MM drugs eventually. Therefore, it is crucial to explore the progression of MM development and the mechanisms related to drug resistance. In this study, we analyzed the gene expression of the dynamic process from normal plasma cell (NPC) to malignant profiling PC by weighted gene co-expression network analysis (WGCNA), found that abnormal gene expression was mainly concentrated in the proteasome. Besides, we found that the expression of PSMB7 could distinguish the different stages of plasma dyscrasia and highest expressed in ISS Ⅲ. Moreover, in the bortezomib (BTZ) treatment group, NDMM patients with high PSMB7 expression had a shorter survival time, and the expression of PSMB7 in the BTZ treatment group was significantly higher than that in the thalidomide (Thai) treatment group. In summary, we found that PSMB7 is the key gene associated with MM disease progression and drug resistance.